ENDOGENOUS GROWTH MODEL: EVIDENCE FROM EAST EUROPEAN COUNTRIES - Mahir Hrnjić; Azra Branković (Economic Review)
Fiscal policy is one of the key issues for every government. In the endogenous growth model, fiscal policy is included as a key factor determining the growth of the economy. The focus in this study is placed on eleven East European transitional countries for the period of 1995 to 2014. The model includes both sides of government finance, taxation and expenditures, with expenditures being grouped into homogeneous categories in order to increase the structural efficiency. We find a positive impact on growth for certain government expenditures such as expenditures aimed at improving human resources, property protection and social investment and a negative one for distortionary taxation. The results provide empirical evidence for the theoretical predictions of endogenous growth.